The relationship between housing investment and economic growth in China: A panel analysis using quarterly provincial data - Jie Chen; Aiyong Zhu (Uppsala University, Department of Economics, 2008)
In this paper we investigate the long-run and short-run relationship between housing investment and economic growth in China using the quarterly province-level panel data for the period 1999 q1 to 2007 q4. Recently developed econometric techniques for panel unit root testing and heterogeneous panel cointegration analysis are employed. The empirical results provide clear support of a stable long-run relationship between housing investment, non-housing investment and GDP in China. We then estimate the long-run elasticity of GDP with respect to housing investment for the whole country as well as three sub regions. The variations across regions are detected and reasons for this fact are discussed. Based on the panel ECM, we show that there is bidirectional Granger causality between housing investment and GDP in both short run and long run for the whole country, while the impacts of housing investment on GDP behave strikingly differently in the three sub-regions of China.
urn:nbn:se:uu:diva-87095
Keywords: E22; L74; R31; 330; Housing investment; Economic growth; Panel cointegration; Granger causality; Wohnungsbauinvestition; Wirtschaftswachstum; Panel; Kausalanalyse; China